Temporal perception is distorted by submaximal and maximal isometric contractions of the knee extensors in young healthy males and females - Gardner, Hayley R.; Konrad, Andreas; Alizadeh, Shahab; Graham, Andrew; Behm, David G. (Frontiers in Sports and Active Living, 2023)
Introduction The estimate of time (temporal perception) is important for activities of daily living, sports and even survival, however time perception research needs greater scrutiny. Time estimation can influence movement decisions and determine whether the individual is successful at their goal, The objectives of this study were to examine participants perception of time at 5-, 10-, 20-, and 30-s intervals to determine possible distortions of time estimates caused by varying intensity isometric contractions, and sex differences. Methods In this repeated measures study, 19 participants (10 females, 9 males) endured two sessions, which consisted of a cognitive task of estimating time intervals while performing an isometric knee extension at maximal, submaximal (60%), and distraction (10%) intensities and a non-active control. In addition to time estimates; heart rate (HR), tympanic temperatures and electromyography during the intervention contractions were monitored. Maximal contractions induced significantly greater time underestimations at 5-s (4.43 ± 0.93, p = 0.004), 20-s (18.59 ± 2.61-s, p = 0.03), and 30-s (27.41 ± 4.07-s, p = 0.004) than control. Submaximal contractions contributed to time underestimation at 30-s (27.38 ± 3.17-s, p = 0.001). Females demonstrated a greater underestimation of 5-s during the interventions than males (p = 0.02) with 60% submaximal (−0.64-s ± 0.26) and distraction (−0.53-s ± 0.22) conditions. For the other 10-, 20-, 30-s intervals, there was no significant time perception sex differences. The control condition exhibited lower HR (75.3 ± 11.6) than the maximal (92.5 ± 13.9), 60% submaximal (92.2 ± 14.4) or distraction (90.5 ± 14.7) conditions. Tympanic temperatures were not influenced by the contraction intensities. Discussion There was greater integrated knee extensor electromyographic activity during the maximal contractions to suggest greater neuromuscular activation that may influence time perception. However, there was no consistent effect of changes in HR or temperature on time estimates. This work adds to the growing literature of time perception during exercise to state that time is significantly underestimated when performing moderate to vigorous intensity exercise.